Development of Canva-Based Interactive Learning Media to Enhance MTs Students’ Understanding of Statistical Concepts - Nisa, Rafika; Rosimanidar; Setiawan, Setiawan (Ar-Riyadhiyyat: Journal of Mathematics Education, 2025)
This research aims to develop Canva-based interactive learning media to improve students' understanding of concepts in statistics materials at the MTs level. The research method used is Research and Development (R&D) by adapting the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model). The research subjects consisted of MTs grade IX students who participated in a small trial of 5 students and a large trial of 20 students. Data collection instruments include expert validation sheets, student response questionnaires, interviews, and pretest and posttest questions to measure understanding of concepts. The validation results showed media feasibility with a score of 84% (material experts) and 86% (media experts), so it was categorized as very good. The results of the small trial test with N-Gain obtained an average result of 0.90 in the high category and the results of the large trial test with N-Gain obtained an average result of 0.81 with the high category, The results of the response questionnaire in the small trial were 95.4% of the very good category. The results of a large trial test with an N-Gain of 0.81 in the high category, It can be concluded that Canva-based interactive learning media is effective and very feasible in improving students' understanding of concepts in statistical material.